2019
DOI: 10.1152/ajpgi.00005.2019
|View full text |Cite
|
Sign up to set email alerts
|

LINC01018 confers a novel tumor suppressor role in hepatocellular carcinoma through sponging microRNA-182-5p

Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related mortality. Emerging evidence has demonstrated that some long noncoding RNAs (lncRNAs) are involved in the development and progression of HCC. Herein, the current study aimed to explore the potential mechanism of LINC01018 in regulating the progression of HCC. Initially, the expression of LINC01018, microRNA-182-5p (miR-182-5p), and forkhead box protein O1 (FOXO1) was quantified in 72 paired HCC and adjacent normal tissue samples as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…F11-AS1 can inhibit HBV-related hepatocellular carcinoma progression by regulating NR1I3 via binding to microRNA-211-5p. LINC01018 has a novel tumor suppressor role in hepatocellular carcinoma by sponging miR-182-5p [9,10]. We also found lower expression of m 6 A-modified MIR325HG to be correlated with worse patient survival in both LGG and GBM (Fig.…”
Section: Association Of M 6 A-modified Te Lncrnas With Tumor Prognosissupporting
confidence: 56%
“…F11-AS1 can inhibit HBV-related hepatocellular carcinoma progression by regulating NR1I3 via binding to microRNA-211-5p. LINC01018 has a novel tumor suppressor role in hepatocellular carcinoma by sponging miR-182-5p [9,10]. We also found lower expression of m 6 A-modified MIR325HG to be correlated with worse patient survival in both LGG and GBM (Fig.…”
Section: Association Of M 6 A-modified Te Lncrnas With Tumor Prognosissupporting
confidence: 56%
“…LINC01363, which is related to worse prognosis, has been shown to be upregulated in breast, ovarian, and cervical cancer [ 19 ]. However, most interestingly, LINC01018, which was associated with a worse response to initial chemotherapy in our model, has been linked to progression in hepatocellular carcinoma (HCC) [ 20 ]. LINC01018 is downregulated in HCC, thereby decreasing the expression of FOXO1, which prevents apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01018, also called SRHC, was down-regulated in HCC, corroborating the findings of Zheng et al 53 that found lower levels of expression in HCC samples with a high serum a-fetoprotein level and a low degree of differentiated tumors. In addition, up-regulation of LINC01018 was shown to decrease proliferation while promoting apoptosis of HCC cells 54 . LINC02027 (alias LOC728290) was found down-regulated in HCC, as also observed by Zhang et al 55 .…”
Section: Resultsmentioning
confidence: 98%